Do seed transfer zones for ecological restoration reflect the spatial genetic variation of the common grassland species Lathyrus pratensis?. Issue 4 (25th October 2017) - Listl, Daniela; Poschlod, Peter; Reisch, Christoph
Abstract : A common ecological restoration approach is the reestablishment of vegetation using seed mixtures. To preserve the natural genetic pattern of plant species local seed material should be used. Consequently, seed transfer zones (seed production areas and seed provenance regions) have been delineated for ecological restoration in Germany. Although it is assumed that these transfer zones represent genetic variation, there remains a lack of empirical data. In this study, we analyzed whether seed transfer zones reflect the genetic variation of the common grassland species Lathyrus pratensis . We sampled 706 individuals from 37 populations in Bavaria, Germany and analyzed genetic variation using amplified fragment length polymorphisms. In our study, we observed higher levels of genetic variation and fragment rarity in the southern Bavarian populations compared to northern populations. Our analyses revealed a strong genetic differentiation between southern and northern Bavarian populations delineated along the Danube River. However, seed production areas and seed provenance regions reflected genetic variation of L. pratensis only to a limited degree. Our study illustrates that the level of genetic variation within populations strongly depends on population history. Furthermore, the geomorphological and climatic attributes, which have been used to delineate seed provenance regions, do not reduce gene flow among populations. Seed collections for gene banks and seed production should comprise seeds from populations in southern and northern Bavaria representing the strong genetic variation between both regions, but prioritize southern populations due to higher levels of variation.